EVALUASI KEBUTUHAN LUAS TERMINAL PENUMPANG TAHUN 2041 MENGGUNAKAN METODE REGRESI LINIER DI BANDAR UDARA KALIMARAU BERAU - Rizky Anggraini; Fahrur Rozi; Supriadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The passenger domestic terminal capacity at Kalimarau Airport with an area of 10.462 m2, currently is only able to accommodate 572 passengers on peak hours. A well-designed terminal development planning would be needed to analyze the needs of domestic terminal space with a supporting data of passengers in the last 5 years, in order to create a sense of comfort and prevent the passenger accumulation in 2041. The aims of this research are to predict the total passenger and to calculate the domestic terminal space capacity needs at Kalimarau Airport in 2041. The method used in processing passenger data for the last 5 years is the Linear Regression Method which is used to predict the number of passengers and passengers during peak hours for the next 20 years. The result of the passenger forecast shows that in the peak hour there will be 435 departing passangers and 418 arriving passangers. With a total of 1.7 million passengers in 2041, a 3.242 m2 domestic terminal space expansion is a need, which consists of 1.847 m2 of departure area and 1.395 m2 of arrival area. So, it can be concluded that the needed space of domestic terminal at Kalimarau Airport in 2041 is 13.6703 m² with passenger flow and space layout planned in such a way as to make it easier for passengers to enjoy the facilities provided.